A Detailed Comprehensive Role of Digital Technologies in Green Finance Initiative for Net‐Zero Energy Transition - Furkan Ahmad (709809) (2025)
This review explores the transformative potential of digital technologies in advancing green finance initiatives to support net‐zero energy transitions. It examines how innovations in FinTech, blockchain, artificial intelligence, and the Internet of Things drive innovation in financing mechanisms, enhance transparency, and improve operational efficiencies across critical sectors, including renewable energy, carbon reduction, lower energy consumption, green industrial transformation, low‐carbon technologies, and sustainable infrastructure including electric vehicles and green buildings. Further, this review addresses challenges associated with implementing these technologies, such as data security risks, regulatory inconsistencies, and unequal access to digital tools. Additionally, this article provides several real‐life case studies and success stories, as well as actionable recommendations that can help develop scalable, equitable, and transparent green finance solutions. The results of this study further highlight the critical interplay between digital technologies and low‐carbon financing initiatives, which can play a critical role in driving a sustainable, low‐carbon future by reducing carbon emissions. Other Information Published in: Advanced Energy and Sustainability Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/aesr.202500066